Effect of Microstructure on The Corrosion Resistance of Duplex Stainless Steels: Materials Performance Maps - Iannuzzi, Mariano; Bernås, M.; Westermann, I.; Lauritsen, C.; Johnsen, R. (2017)
Although duplex stainless steels are extensively used in oil and gas production due to their excellent combination of mechanical properties and corrosion resistance, they are susceptible to precipitation of deleterious phases during heat treatment and manufacturing operations. Deleterious phases affect both localized corrosion resistance and mechanical properties. Even though current international standards such as ISO 21457, NORSOK M-001 and NORSOK M-630 treat most 25Cr duplex stainless steel (SDSS) grades as equivalent, debate still exists as to whether alloying elements such as tungsten accelerate or retard the formation of detrimental phases. Understanding the effect of alloying elements on phase transformation kinetics can help streamline fabrication by optimizing, for example, welding procedures. In this work, the effect of W on the precipitation kinetics of a 25% Cr SDSS, namely, UNS S32760 was quantified by constructing Time-Temperature-Transformation (TTT) diagrams. The effect of tertiary phases on localized corrosion resistance was investigated as a function of volume fraction and type of precipitate, with a focus on s- and ?- phase formation. The critical pitting temperature (CPT) of the various metallurgical stages was determined by monitoring open circuit potentials during immersion in 6 wt% ferric chloride (FeCl3). Materials performance maps (MPM) were developed by combining TTT diagrams with CPT. Given that MPM provide information about phase transformation kinetics and corrosion resistance simultaneously, TTT-CPT diagrams could become an indispensable materials selection tool that could be incorporated as parts of international materials selection standards.